Korelasi Antara Pelayanan Keperawatan Berbasis Spiritual dengan Tingkat Kepuasan Kerja Perawat - Fika Rahmatul Umah; Dyah Wiji Puspita Sari; Retno Issroviatiningrum (Protein : Jurnal Ilmu Keperawatan dan Kebidanan., 2025)
This research seeks to examine the connection between spiritual-based nursing services and nurses' job satisfaction at the Sultan Agung Islamic Hospital Semarang. Job satisfaction, which is influenced by various aspects, plays an important role in improving nurse work efficiency and service quality. This study employed a quantitative methodology with an analytical survey and a crosstab study on 100 implementing nurses, using a total sampling technique. Data was collected through questionnaires and analyzed with Chi Square statistical tests. As many as 66% of respondents rated spiritual-based services in the good category, and 54% were satisfied with their work. The analysis showed a notable correlation between spiritually integrated services and nurses' workplace fulfillment ( P Value < 0.05; r = 0.696). Applying well-structured spiritual-based nursing services enhances nurses' job satisfaction. These findings can support the development of strategies to improve nursing services as well as their professional performance.